The role of pedagogical content knowledge on giving meaning to the multiplication of fractions. A case study in Mexico - Páez, David Alfonso; Medina Mendoza , Indira Viridiana; Pérez-Martínez , María Guadalupe (Educação Matemática Debate, 2023)
This paper aims to describe the pedagogical content knowledge when teaching the multiplication of fractions in elementary education. A sixth-grade teacher was observed and interviewed while working on this topic with students in a Mexican public school. As a part of the analysis, categories were derived from the literature and emerging subcategories from the data were implemented. The resulting categories were: knowledge for teaching fraction multiplication, knowledge of features of learning mathematics, and knowledge of fraction multiplication learning standards. The results show that teacher’s pedagogical knowledge is characterized by pedagogical strategies oriented to promote the learning of this mathematical object, the strategies that stood up from the rest are making discoveries and inferences as well as using strips of paper and geometrical figures to manipulate and visualize the multiplication of fractions algorithm. Through these strategies, the teacher gave the meaning of part of a whole and repeated addition to the multiplication of fractions.